The Influence Of Firm Size, Firm Age and Leverage On Intellectual Capital Disclosure - Muhammad Farhan Baihaki; Leny Suzan (International Journal of Economics Development Research (IJEDR), 2025)
The disclosure of intellectual capital an intangible asset category governed by PSAK No. 19 (Revised 2009) is typically reported within a firm’s annual report. Such reporting customarily addresses three principal dimensions: human capital, structural capital, and relational capital. This research investigates whether firm size, firm age, and financial leverage exert significant effects on the extent of intellectual capital disclosure. The study population comprises property and real-estate firms listed on the Indonesia Stock Exchange over the 2020–2024 period. Using purposive sampling, the research selects 33 firms, yielding 165 panel observations. A quantitative methodology and panel regression analysis are implemented with EViews 12 to test the hypotheses. The findings are intended to illuminate determinants of intellectual capital disclosure for practitioners and to underscore the need for firms to monitor evolving disclosure requirements and standards pertaining to intangible informatio.